2017
DOI: 10.1016/j.pec.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The importance of acknowledgement of emotions in routine patient psychological assessment: The example of the dental setting

Abstract: The importance of acknowledgement of emotions in routine patient psychological assessment Hally, J.; Freeman, R.; Yuan, S.; Humphris, G. General rightsCopyright and moral rights for the publications made accessible in Discovery Research Portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from Discovery Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
2
25
0
2
Order By: Relevance
“…Hally et al, 19 using video recordings, showed that if a dentist discussed the patient's MDAS result with the patient during the first few minutes of the appointment the extremely dentally anxious patient was less anxious 3 months later. 19 Therefore, the dentist's awareness and knowledge of dental anxiety together with effective communication skills allow the dentist to speak to the patient about their fears, make the treatment alliance and reduce dental anxiety. It may be suggested that clinical communication skills should be taught as part of behavioural management of dental anxiety to undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…Hally et al, 19 using video recordings, showed that if a dentist discussed the patient's MDAS result with the patient during the first few minutes of the appointment the extremely dentally anxious patient was less anxious 3 months later. 19 Therefore, the dentist's awareness and knowledge of dental anxiety together with effective communication skills allow the dentist to speak to the patient about their fears, make the treatment alliance and reduce dental anxiety. It may be suggested that clinical communication skills should be taught as part of behavioural management of dental anxiety to undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…31 In view of the fear expressed by TDI patients, it may be useful for dentists to include psychological assessments as part of their routine practice to better alleviate stress and anxiety in their patients. Hally and coworkers 32 suggested that engaging patients to discuss and understand their experiences is a strategy dentists should adopt during their routine dental practice.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the exchange between dental professionals and the patient. [24][25][26][27][28][29][30][31][32] The second concentrates on Intraprofessional Education or "IPE" Intraprofessional education or "IPE." 5,20,29,[33][34][35][36][37][38][39] The third area of communication literature that is prominent in the discourse is that of treatment outcomes or "patient-centred" care.…”
Section: Previous Literaturementioning
confidence: 99%
“…Communication literature concerning oral health practitioners is most often disseminated into one of four categories. The first is the exchange between dental professionals and the patient . The second concentrates on Intraprofessional Education or “IPE” Intraprofessional education or “IPE.” The third area of communication literature that is prominent in the discourse is that of treatment outcomes or “patient‐centred” care .…”
Section: Introductionmentioning
confidence: 99%